2013
DOI: 10.14260/jemds/1118
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesic Efficacy of Intrathecal Tramadol Versus Nalbuphine Added to Bupivacaine in Spinal Anaesthesia for Lower Limb Orthopaedic Surgery

Abstract: BACKGROUND: Effect of adding intrathecal tramadol and nalbuphine to local anaesthetics in spinal anaesthesia is not much studied. STUDY DESIGN: A prospective, randomised double blind placebo controlled study. METHODS: 90 adult patients of ASA grade I-II scheduled for lower limb orthopaedic surgery under spinal anaesthesia were randomised to three groups of 30 each destined to receive 2.5ml (12.5mg) hyperbaric bupivacaine (0.5%) along with 1 ml of either normal saline (Group C) 50mg tramadol (Group T) or 2mg na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…(8) In our study nalbuphine added as adjuvant to ropivacaine is found to be more potent and efficacious. In a similar study by Verma (25) in 2013 proved that nalbuphine when added to bupivacaine intrathecally improves postoperative analgesia, which is consistent with our result. In table 4, results did not show any statistically significant difference for mean heart rate at pre-operatively (p=0.146) and at baseline (p=0.677).…”
Section: Equipotency Of Dose Of Epidural Ropivacainesupporting
confidence: 91%
“…(8) In our study nalbuphine added as adjuvant to ropivacaine is found to be more potent and efficacious. In a similar study by Verma (25) in 2013 proved that nalbuphine when added to bupivacaine intrathecally improves postoperative analgesia, which is consistent with our result. In table 4, results did not show any statistically significant difference for mean heart rate at pre-operatively (p=0.146) and at baseline (p=0.677).…”
Section: Equipotency Of Dose Of Epidural Ropivacainesupporting
confidence: 91%
“…Verma et al . [ 16 ] showed that postoperative analgesia was significantly improved by the addition of nalbuphine. Mostafa et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the analgesic effects of morphine and nalbuphine, a synthetic opiate with mixed agonist-antagonist actions, have been reported [56]. As a novel opioid κ receptor agonist-antagonist, nalbuphine, can agitate the κ receptors to achieve a superior analgesic effect and antagonize the μ receptors to reduce the incidence of adverse reactions [78].…”
Section: Introductionmentioning
confidence: 99%